2016
DOI: 10.1111/ajt.13827
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Trends in United States Living Kidney Donors (2004 to 2015)

Abstract: Some transplant programs consider the lack of health insurance as a contraindication to living kidney donation. Still, prior studies have shown that many adults are uninsured at time of donation. We extend the study of donor health insurance status over a longer time period and examine associations between insurance status and relevant sociodemographic and health characteristics. We queried the UNOS/OPTN registry for all living kidney donors (LKDs) between July 2004 and July 2015. Of the 53,724 LKDs with known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The potential for an interruption in employment or loss of employment may pose a greater concern for loss of work-related benefits, including health insurance, in men. Ensuring adequate medical follow-up for living donors postdonation is increasingly recognized a priority for transplantation programs, 22,23 and therefore lack of health insurance may be a significant barrier to donation. Because a larger proportion of women in the United States have their health insurance benefits covered as a dependent, 24 the threat of job loss may not necessarily affect their ability to access health care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for an interruption in employment or loss of employment may pose a greater concern for loss of work-related benefits, including health insurance, in men. Ensuring adequate medical follow-up for living donors postdonation is increasingly recognized a priority for transplantation programs, 22,23 and therefore lack of health insurance may be a significant barrier to donation. Because a larger proportion of women in the United States have their health insurance benefits covered as a dependent, 24 the threat of job loss may not necessarily affect their ability to access health care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, lack of access to health insurance may have presented a barrier to PCP utilization for some donors. A study of donor health insurance by Rodrigue and colleagues reported that 16% of donors were uninsured at the time of donation; young donors, male donors, and nonwhite donors were at increased risk of lacking health insurance . Our group has previously reported difficulties among live kidney donors in obtaining or changing health insurance after donation .…”
Section: Discussionmentioning
confidence: 73%
“…528,530,531 Lack of health insurance had been more common among living kidney donors in the United States than in the general US population, although that disparity has not been present in recent years, perhaps due to changes in the economy and policy changes including the Patient Protection and Affordable Care Act (ACA). 533,534 Lack of insurance and lower educational attainment may pose lesser obstacles to follow-up in other countries where national healthcare is available. Among US centers in 2008 to 2012, large annual living donation volumes were also associated with increased rates of follow-up deficiencies.…”
Section: Follow-up Timing and Processesmentioning
confidence: 99%